CIAT - World food price rises 2011 - International Center for Tropical Agriculture (2011)
CIAT's Agricultural Policy Economist Bernardo Creamer talks about the recent rises in world food prices, and compares the situation now with the world food price crisis of 2006-2008. He also talks about the importance of improving agricultural research and development to buffer the impact of adverse weather and climate change on food production, and therefore food prices.